Open University Malaysia : way forward in Science and Technology education - Thirumeni Subramaniam ,; Sharifah Rosfashida Syed Abd Latif ,; Kanesan Muthusamy,; Mukherjee, T. K; Mohd Kidin Shahran, (2008)
One of Malaysia’s national agenda is to move towards a scientific and progressive society. Government strategies for Malaysia described in this paper highlights the importance of life long learning in achieving its national agenda. Open University Malaysia as a pioneer in open and distance education has a role in promoting life long learning in Malaysia. This paper highlights the key features of the university i.e. blended learning mode and e-learning platform which offers various benefits that could provide supports for creating an innovative society. In the context of science and technology, creating an innovative society means creating manpower with good foundation in basic science knowledge and science skills, a sense of appreciation of contributions and innovations in science and technology, positive attitudes and awareness on ethical issues. This paper proposes strategies to invest in the future by retraining man-power, promoting basic science and increasing the quality of technical courses. (Authors' abstract)